2015
DOI: 10.1016/j.neuroscience.2015.03.067
|View full text |Cite
|
Sign up to set email alerts
|

The role of TRPM2 in hydrogen peroxide-induced expression of inflammatory cytokine and chemokine in rat trigeminal ganglia

Abstract: Trigeminal ganglia (TG) contain neuronal cell bodies surrounded by satellite glial cells. Although peripheral injury is well known to induce changes in gene expression within sensory ganglia, detailed mechanisms whereby peripheral injury leads to gene expression within sensory ganglia are not completely understood. Reactive oxygen species (ROS) are an important modulator of hyperalgesia, but the role of ROS generated within sensory ganglia is unclear. Since ROS are known to affect transcription processes, ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 42 publications
4
42
0
Order By: Relevance
“…Which, then, are the possible mechanisms of H 2 O 2 ‐induced activation of nociceptors? Either direct receptor activation by H 2 O 2 or indirect mechanismssuch as the formation of downstream lipid peroxidation products activating TRP channels or increased expression of pro‐inflammatory cytokines and chemokines might explain the actions of H 2 O 2 (Keeble et al ., ; Chung et al ., ). Direct activation of TRPA1 channels by H 2 O 2 is mediated by H 2 O 2 ‐derived hydroxyl radicals (see Ogawa et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Which, then, are the possible mechanisms of H 2 O 2 ‐induced activation of nociceptors? Either direct receptor activation by H 2 O 2 or indirect mechanismssuch as the formation of downstream lipid peroxidation products activating TRP channels or increased expression of pro‐inflammatory cytokines and chemokines might explain the actions of H 2 O 2 (Keeble et al ., ; Chung et al ., ). Direct activation of TRPA1 channels by H 2 O 2 is mediated by H 2 O 2 ‐derived hydroxyl radicals (see Ogawa et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, reactive oxygen species (ROS) released in response to tissue damage during inflammation can either directly activate TRPA1 (Macpherson et al, 2007) or could lead to the production of endogenous agonists by lipid peroxidation (Trevisani et al, 2007). Recently, we showed that ROS is released within TG following masseter inflammation, which could lead to direct or indirect activation of TRPA1 within TG (Chung, 2015). Therefore, a sustained elevation of ROS in the damage tissue could potentially maintain TRPA1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…ROS levels were determined using H2DCFDA (Invitrogen, Carlsbad, CA) according to the protocol previously described (Chung et al, ). Briefly, rats were injected with vehicle or complete CFA in isotonic saline into the masseter muscle.…”
Section: Methodsmentioning
confidence: 99%
“…ROS levels were determined using H2DCFDA (Invitrogen, Carlsbad, CA) according to the protocol previously described (Chung et al, 2015).…”
Section: Ros Assaymentioning
confidence: 99%